Insider status: (Re)framing researcher positionality in international human resource management studies. (May 2020) - Collins, Heidi; McNulty, Yvonne
Insider researchers in international human resource management study not only the organisations or communities they may be members of, but also the people they perceive closeness with or with whom they share identities. The research context for insiders is rich but rarely problem-free. The uncertainty and dynamism of insider research often leaves insider researchers grappling with methodological and ethical challenges, but with no explicit framework to guide how they can be addressed in research practice or research reporting. Indeed, the 'sanitised' methodologies appearing in published work often do not reflect the complexity of the authors' experience. In this article, we call for researchers to give more explicit consideration of what it means to research from an insider position, regardless of the research paradigm from which they work. The article addresses some of the messy details of insider research, drawing on personal accounts of our own research practice. We offer a framework of researcher personae as a tool for reflecting upon researchers' insider positionality before, during and after data have been collected and analysed. Overall, we encourage researchers working from insider positions to adopt three practices: (1) to engage in reflexive consideration of the effects of (changing) positionality on their work as a way to strengthen the ethical and theoretical outcomes of research practice; (2) to acknowledge and leverage, rather than conceal, insiderness as a key strategy for making feasible more research on sensitive and 'taboo' topics; and (3) to make positionality explicit in research reporting in order to enhance the quality of insider research as well as enhance fieldwork learning more generally in the international human resource management field. While the personal accounts we share in this article are based on our research within the field of international human resource management, the intention is that it may also be of value to researchers in other fields.